Design and Testing of Stream as a Sterilization Tool for Trichoderma sp. Propagation Media Using a Palm Oil Mill Steam Boiler - Fajri, Ihsanul; Hartulistiyoso, Edy; Widyastuti, Rahayu (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Trichoderma sp. is a fungus used in oil palm plantations to control basal stem rot disease, which can reduce palm oil production by up to 80%. At PT. Bumitama Gunajaya Agro, the production of this fungus uses an autoclave, which can only produce 51 kg of Trichoderma sp. per day per unit. To meet the high demand for Trichoderma sp., a large-capacity sterilization tool called "stream" is needed for mass production. The optimal performance of the Stream shows that effective sterilization can be achieved in 20 min when the tool is operated for 45 min. The effectiveness of this sterilization time is proven by the Total Plate Count (TPC) test, which shows a bacterial count of 109×103 CFU/g and a fungal count of 35 CFU/g. The Trichoderma sp. product produced through this process has a conidium density of 8×108, 100% conidium viability, and an inhibition power of 54%, all of which exceed the standard values of SNI 8027.3:2014. Based on its production capacity, Stream can achieve production of up to 1 ton per day with quality not significantly different from Trichoderma sp. production using an autoclave. Keywords: Autoclave, Basal stem rot disease, Sterilization, TPC, Trichoderma sp.